Characterization of Fowler-Nordheim Tunneling and Temperature Effects in Metal-Oxide-Semiconductor Structures Using Vertical Optimization - S. Toumi; T. Guerfi (Current Research Progress in Physical Science Vol. 5, 2024)
The objective of this chapter book is to investigate the transport charge carriers responsible for the Fowler-Nordheim current type and to analyze the temperature effect on the different parameters that characterize this class of transport process. These parameters are the effective mass of charge carriers in the oxide (mox), the effective mass of charge carriers in the semiconductor (msc), the barrier height of charge carriers (\(φ\)B), and the corrected oxide voltage (Vcorr). To determine the above-cited parameters, the vertical optimization method (VOM) on the current-voltage curves as a function of temperature was used. Contrarily to other methods used previously, simultaneously those parameters were extracted, whereas the others have to use known mox and msc to determine \(φ\)B or vice versa, moreover, the correction of the oxide voltage is taken from literature or calculated from the capacitance-voltage curves or the Mott-Schottky equation or other procedures. The VOM is insensitive to the errors associated with measurements and represents a remarkable degree of accuracy and robustness. The influence of temperature on the characterized parameters of the studied structure offers insights into the conditions of the oxide/semiconductor interface and provides guidance for optimizing circumstances in specific oxide and semiconductor applications. Additionally, this investigation serves as a useful tool for future technological applications of oxides and provides valuable considerations for fabricating MOS structures.